Real Time Control Engineering Systems And Automation - Ng, Tian Seng (Studies in Systems, Decision and Control, 2016)
This book covers the two broad areas of the electronics and electrical aspects of control applications, highlighting the many different types of control systems of relevance to real-life control system design. The control techniques presented are state-of-the-art. In the electronics section, readers will find essential information on microprocessor, microcontroller, mechatronics and electronics control. The low-level assembly programming language performs basic input/output control techniques as well as controlling the stepper motor and PWM dc motor. In the electrical section, the book addresses the complete elevator PLC system design, neural network plant control, load flow analysis, and process control, as well as machine vision topics. Illustrative diagrams, circuits and programming examples and algorithms help to explain the details of the system function design. Readers will find a wealth of computer control and industrial automation practices and applications for modern industries, as well as the educational sector.